2020
DOI: 10.1111/obr.13108
|View full text |Cite
|
Sign up to set email alerts
|

Adropin as a potential mediator of the metabolic system‐autonomic nervous system‐chronobiology axis: Implementing a personalized signature‐based platform for chronotherapy

Abstract: Adropin is a peptide hormone, which plays a role in energy homeostasis and controls glucose and fatty acid metabolism. Its levels correlate with changes in carbohydratelipid metabolism, metabolic diseases, central nervous system function, endothelial function and cardiovascular disease. Both metabolic pathways and adropin are regulated by the circadian clocks. Here, we review the roles of the autonomic nervous system and circadian rhythms in regulating metabolic pathways and energy homeostasis. The beneficial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 140 publications
1
49
0
Order By: Relevance
“…Regular fixed regimens for the administration of chronic drugs may not be compatible with physiological variabilities in biology, and this can underlie the loss of response to chronic drugs [ 26 , 28 , 47 , 48 , 49 ]. However, introducing variability into therapeutic regimens can improve the response to drugs [ 26 , 27 , 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Dose escalations, reductions, and intermittent dosing with drug holidays exert clinical benefits while minimizing adverse effects [ 20 , 60 , 61 , 62 , 63 ].…”
Section: Second-generation Ai Systems: Focus On Improving Clinicalmentioning
confidence: 99%
See 3 more Smart Citations
“…Regular fixed regimens for the administration of chronic drugs may not be compatible with physiological variabilities in biology, and this can underlie the loss of response to chronic drugs [ 26 , 28 , 47 , 48 , 49 ]. However, introducing variability into therapeutic regimens can improve the response to drugs [ 26 , 27 , 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ]. Dose escalations, reductions, and intermittent dosing with drug holidays exert clinical benefits while minimizing adverse effects [ 20 , 60 , 61 , 62 , 63 ].…”
Section: Second-generation Ai Systems: Focus On Improving Clinicalmentioning
confidence: 99%
“…A prospective trial of patients with inflammatory bowel disease treated with anti-TNFs showed a loss of clinical response in 36% of patients on fixed dosing, compared with only 13% in patients on variable dosing regimens [ 64 ]. Real-world data support the beneficial effects of drug holidays and dose escalation/reduction [ 24 , 28 , 29 , 49 , 50 , 54 , 55 , 56 , 57 , 65 , 66 ]. Introducing variability into biological systems may improve their overall function and correct dysfunctions that underlie diseases [ 26 , 67 ].…”
Section: Second-generation Ai Systems: Focus On Improving Clinicalmentioning
confidence: 99%
See 2 more Smart Citations
“…Ignoring this problem is associated with lower effectiveness in many drugs used for chronic conditions, Ilan J Transl Med (2021) 19:55 sometimes in up to 40% of patients, such as those with epilepsy or depression, where many patients develop drug resistance [20,21]. Thus, next-generation translation research is required to provide a way to deal with compensatory responses [22][23][24][25][26][27][28][29][30].…”
Section: Next-generation Translational Research: Translating the Innomentioning
confidence: 99%